The impact of field cancerization on the extent of duct carcinoma in situ (DCIS) in breast tissue after conservative excision. Issue 12 (December 2016) - Asioli, S.; Morandi, L.; Cavatorta, C.; Cucchi, M.C.; Foschini, M.P.
Abstract: Aim: Aim of the present study is to evaluate the risk of residual neoplastic foci, in patients treated with breast conservative surgery, based on duct carcinoma in situ (DCIS) grading. Materials and methods: The study is based on a retrospective analysis of 419 resection specimens relative to 161 patients. All these patients underwent surgical re-excision when the first specimen had shown one or more margins involved by DCIS. Margins were oriented and the side of margin involved was recorded. Clonal analysis, using the mitochondrial DNA (mtDNA) technique, was obtained in selected cases. Results: Residual neoplastic foci were found in 145 out of 419 (34.6%) re-excised specimens. Specifically, residual foci of DCIS grade 2 and 3 were found more frequently in the margin facing the nipple (33.3% and 51.6%, respectively). On the contrary foci of DCIS grade 1 did not show any specific distribution. Clonal mt DNA analysis evidenced that DCIS grade 3 foci present in the re-excision specimens were genetically similar to the tumor removed in the first specimen, while DCIS grade 1 foci were not clonally related each other. Conclusions: The present data further confirm that DCIS grade 3 is characterized by a circumscribed neoplastic process extending along the large ducts probably of a single mammary lobe. On the contrary DCIS grade 1 is characterized by multiple independent neoplastic foci, dispersed through several lobes indicating a field where multiple independent foci of cancer harbor.